NILAI NILAI KEPRIBADIAN TOKOH MINKE DALAM ROMAN BUMI MANUSIA KARYA PRAMOEDYA ANANTA TOER - Ichsan, Muhammad Hidayatul (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2020)
ABSTRACTMinke Figure in the Roman Earth Human Earth The work of Pramoedya Ananta Toer can be drawn in the following extracts: This study aims to find out the main characters in Roman language, the character used is Minke. Another goal is to find out the story of Minke's struggle with the Colonial people and also the romance between Minke and Annelies. The results that can be analyzed by Minke have characters such as: Smart, caring, full of struggle, humane, merciful, polite, brave, obedient to parents, sincere. Minke is a priyayi-blooded native figure who always upholds priority values above all. When his native people were being oppressed by Europeans Minke was a figure who fought for these values, he was supported by Nyai Ontosoroh in freeing his people from the cruelty of European nations. He was a revolutionary figure who changed the way people think when indigenous degrees were brought down in front of Europeans. This research uses descriptive method by using qualitative research of the main character in the Roman language of Human Earth by Pramoedya Ananta Toer with scientific theories about personality choosing in the analysis of the main character's character. The technique of receiving data carried out in this study is the method of listening and recording traffic techniques and quoting from various sources in journals and on the internet.Keywords: Minke, Struggle, Character.